2016
DOI: 10.18632/oncotarget.9157
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatocellular carcinoma: an overview of major findings from meta-analyses

Abstract: This paper aims to systematically review the major findings from meta-analyses comparing different treatment options for hepatocellular carcinoma (HCC). A total of 153 relevant papers were searched via the PubMed, EMBASE, and Cochrane library databases. They were classified according to the mainstay treatment modalities (i.e., liver transplantation, surgical resection, radiofrequency ablation, transarterial embolization or chemoembolization, sorafenib, and others). The primary outcome data, such as overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 136 publications
(347 reference statements)
1
41
0
1
Order By: Relevance
“…Despite the major advances achieved in the diagnostic workup of HCC, only one third of the newly diagnosed patients are presently eligible for curative treatments [3]. Even in the curative setting, 5-year survival rates after resection for early-stage HCC ranges between 17% and 53%, and recurrence rates can be as high as 70% [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the major advances achieved in the diagnostic workup of HCC, only one third of the newly diagnosed patients are presently eligible for curative treatments [3]. Even in the curative setting, 5-year survival rates after resection for early-stage HCC ranges between 17% and 53%, and recurrence rates can be as high as 70% [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…With the application of polyvinyl alcohol, trisacryl gelatin microspheres (embospheres; Merit Medical Systems, Inc., South Jordan, UT, USA) and drug‐eluting beads, the common iodized oil TACE technique has been challenged by one that uses microspheres for the treatment of liver tumors . A recent large overview analyzed three meta‐analyses of TACE vs TAE; none of them found any significant difference between the two techniques . However, another study found that, compared to TAE, TACE significantly prolonged progression‐free survival (PFS) and time to progression (TTP), but not overall survival (OS) .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A recent large overview analyzed three meta-analyses of TACE vs TAE; none of them found any significant difference between the two techniques. 5 However, another study found that, compared to TAE, TACE significantly prolonged progression-free survival (PFS) and time to progression (TTP), but not overall survival (OS). 11 Thus, though TAE is reported to be efficacious, the ultimate outcome with TACE is better.…”
Section: Introductionmentioning
confidence: 99%
“…Grade of recommendation was determined in the way that was suggested by a previous study [64]. High grade recommendation was considered if the results of meta-analyses were based on more than 3 single-center RCTs or 1 multi-center RCT.…”
Section: Methodsmentioning
confidence: 99%